Arterial spin labeling MRI is able to detect early hemodynamic changes in diabetic nephropathy. Issue 6 (6th April 2017) - Mora‐Gutiérrez, José María; Garcia‐Fernandez, Nuria; Slon Roblero, M. Fernanda; Páramo, Jose A.; Escalada, F. Javier; Wang, Danny JJ.; Benito, Alberto; Fernández‐Seara, María A.
Abstract : Purpose: To investigate whether arterial spin labeling (ASL) MRI could detect renal hemodynamic impairment in diabetes mellitus (DM) along different stages of chronic kidney disease (CKD). Materials and Methods: Three Tesla (3T) ASL‐MRI was performed to evaluate renal blood flow (RBF) in 91 subjects (46 healthy volunteers and 45 type 2 diabetic patients). Patients were classified according to their estimated glomerular filtration rate (eGFR) as group I (eGFR > 60 mL/min/1.73 m 2 ), group II (60 ≥ eGFR>30 mL/min/1.73 m 2 ), or group III (eGFR ≤ 30 mL/min/1.73 m 2 ), to determine differences depending on renal function. Studies were performed at 3T using a 12‐channel flexible body array combined with the spine array coil as receiver. Results: A 28% reduction in cortical RBF was seen in diabetics in comparison with healthy controls (185.79 [54.60] versus 258.83 [37.96] mL/min/100 g, P < 3 × 10 −6 ). Differences were also seen between controls and diabetic patients despite normal eGFR and absence of overt albuminuria (RBF [mL/min/100 g]: controls=258.83 [37.96], group I=208.89 [58.83], P = 0.0018; eGFR [mL/min/1.73 m 2 ]: controls = 95.50 [12.60], group I = 82.00 [20.76], P > 0.05; albumin‐creatinine ratio [mg/g]: controls = 3.50 [4.45], group I = 17.50 [21.20], P > 0.05). A marked decrease in RBF was noted a long with progression of diabetic nephropathy (DN) through the five stages of CKD (χ 2 = 43.58; P = 1.85 × 10 −9 ). Strong correlation (r = 0.62; P = 4 × 10 −10 ) was obtained between RBF and GFR estimated by cystatin C. Conclusion: ASL‐MRI is able to quantify early renal perfusion impairment in DM, as well as changes according to different CKD stages of DN. In addition, we demonstrated a correlation of RBF quantified by ASL and GFR estimated by cystatin C. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2017;46:1810–1817.